Hubungan Makrosomia, Persalinan induksi, dan Persalinan Lama dengan Kejadian Atonia Uteri di Rumah Sakit TK. II 02.05.01 Dr. AK Gani Palembang tahun 2018 - yani, Turi (Program Studi Ilmu Kesehatan STIKESÂ Abdi Nusa Pangkalpinang, 2018)
Uterine atony is a state of weak muscle tone or uterine contractions that causes the uterus to be unable to close open bleeding from the placenta implantation site after the baby and placenta are born. This study aims to determine the relationship between macrosomia, induced labor, and prolonged labor with the incidence of uterine atony at Tk. II 02.05.01 dr. AK Gani Palembang in 2018. This study used an analytical survey method with a cross sectional approach. The population in this study were all mothers giving birth at the Tk. II 02.05.01 dr. AK Gani Palembang in 2018 totaled 1,375 respondents. The number of samples is 93 respondents, with the technique of taking by systematic random sampling. The results of the univariate analysis showed that respondents diagnosed with uterine atony were 33 (33.3%), macrosomia 17 (18.3%), 41 induced labor (44.1%), and 23 (24.7%) long labor. The statistical test used was the chi-square test. The results of the bivariate analysis showed that there was a significant relationship between macrosomia (Pvalue = 0.006), induced labor (Pvalue = 0.010), and prolonged labor (Pvalue = 0,000) with the incidence of uterine atony at Tk Hospital. II 02.05.01 dr. AK Gani Palembang in 2018. From the results of this study, it is recommended that the hospital continue to provide and improve treatment for patients diagnosed with uterine atony, as well as provide counseling about the dangers that can occur and to reduce maternal mortality in Indonesia.